Peer Selected Modeling: A Rapid Treatment for Aggressive Disruptive Behavior - Hayduk, Allan W. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study reports the successful use of compulsory 'peer selecting modeling' for the treatment of hostile and aggressive behavior within a special education program.The treatment procedure, a brief, situation-specific variant of peer and participant modeling, was designed for routine use by classroom teachers. Use of the treatment resulted in the rapid and complete elimination of peer aggression in the eight participants completing the study. A three month follow up indicated that all in-class improvements were maintained, and in most cases the improved behavior generalized to other classes. Several parents reported simultaneous improvements in the homes.These findings suggest that the procedure can be effective in the rapid treatment ofdisruptive-aggressive behavior in special class situations.